Case report: Local bacteriophage therapy for fracture-related infection with polymicrobial multi-resistant bacteria: hydrogel application and postoperative phage analysis through metagenomic sequencing - Alt, Volker; Gessner, André; Merabishvili, Maya; Hitzenbichler, Florian; Mannala, Gopala Krishna; Peterhoff, David; Walter, Nike; Pirnay, Jean-Paul; Hiergeist, Andreas; Rupp, Markus (Frontiers in Medicine, 2024)
Fracture-related infections can be challenging, particularly with concomitant severe bone defects and multi-resistant microorganisms. We present a case of a 42-year-old patient with a fracture-related infection following a war injury from a gunshot, resulting in a 12-cm subtrochanteric segmental bone defect and the detection of four different multi-resistant Gram-negative bacteria. Due to antibiotic drug resistance, treatment with bacteriophages was considered. Phage susceptibility testing revealed the activity of a commercially available bacteriophage cocktail (Intesti bacteriophage, Eliava Institute, Tbilisi, Georgia). This phage cocktail was included in a modified two-stage Masquelet technique. During the first intervention, the bone was debrided and samples for microbiological and phage testing were harvested. The indwelling intramedullary rod was removed, and the bone defect was filled with a PMMA spacer loaded with colistin and the bone stabilized with a plate. During the second procedure, the PMMA spacer was removed and a silver-coated angular stable plate was implanted. The bone defect was filled with a fibular autograft and allograft cancellous bone chips. At the end of the procedure, the Intesti bacteriophage cocktail was injected into a DAC hydrogel and this bacteriophage hydrogel composite was then put onto the angular stable plate. Postoperatively the wound fluid was collected over 72 h, and high-throughput metagenomic sequencing was performed. This showed a time-dependent release of the bacteriophages in the wound fluid, with a relatively high concentration after 12 h, decreasing to DNA copies of 0 after 72 h. Furthermore, we have assessed the release of phages from DAC gel and the effect of DAC gel on the phages in vitro. The results showed a stable and rapid release of phages from the DAC gel ( 1×103 PFU/mL). The clinical course of the patient showed no relapse of the infection with good bone consolidation of the bone defect after 1 year without the need for any surgical revision. To the best of our knowledge, this is the first case that shows the detection of bacteriophage DNA copies by high-throughput metagenomics sequencing in a patient with a complex fracture-related infection. Successful treatment of this case encourages further investigation of bacteriophage therapy in patients with complex bone and joint infections.